If f ′ ′ ( x ) = − f ( x ) and g ( x ) = f ′ ( x ) and F ( x ) = ( f ( 2 x ) ) 2 + ( g ( 2 x ) ) 2 and given that F ( 5 ) = 5 , find F ( 1 0 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Given f ′ ′ ( x ) = − f ( x ) ⟹ f ( x ) = A sin x + B cos x , where A and B are arbitrary constants, as shown below.
f ( x ) f ′ ( x ) f ′ ′ ( x ) = A sin x + B cos x = A cos x − B sin x = g ( x ) = − A sin x − B cos x = − f ( x )
Then, we have:
F ( x ) ⟹ F ( 5 ) ⟹ F ( 1 0 ) = ( f ( 2 x ) ) 2 + ( g ( 2 x ) ) 2 = ( A sin 2 x + B cos 2 x ) 2 + ( A cos 2 x − B sin 2 x ) 2 = A 2 sin 2 2 x + 2 A B sin 2 x cos 2 x + B 2 cos 2 2 x + A 2 cos 2 2 x − 2 A B sin 2 x cos 2 x + B 2 sin 2 2 x = A 2 ( sin 2 2 x + cos 2 2 x ) + B 2 ( sin 2 2 x + cos 2 2 x ) = A 2 + B 2 Note that F ( x ) is independent of x . = A 2 + B 2 = 5 = 5
Solving for the functions f ( x ) & g ( x ) yields:
f ′ ′ ( x ) + f ( x ) = 0 ⇒ f ( x ) = A c o s ( x ) + B s i n ( x ) and g ( x ) = f ′ ( x ) = − A s i n ( x ) + B c o s ( x ) (where A , B ∈ R ) .
Solving for F ( x ) produces:
F ( x ) = [ f ( x / 2 ) ] 2 + [ g ( x / 2 ) ] 2 = ( A c o s ( x / 2 ) + B s i n ( x / 2 ) ) 2 + ( − A s i n ( x / 2 ) + B c o s ( x / 2 ) ) 2 ;
or A 2 c o s 2 ( x / 2 ) + 2 A B c o s ( x / 2 ) s i n ( x / 2 ) + B 2 s i n 2 ( x / 2 ) + A 2 s i n 2 ( x / 2 ) − 2 A B c o s ( x / 2 ) s i n ( x / 2 ) + B 2 c o s 2 ( x / 2 ) ;
or ( A 2 + B 2 ) ( c o s 2 ( x / 2 ) + s i n 2 ( x / 2 ) ) ;
or F ( x ) = A 2 + B 2 = c o n s t a n t for all x ∈ R . Hence, F ( 1 0 ) = F ( 5 ) = 5 .
@Tom Engelsman , you should put a backslash in front of functions so that they don't appear as italic which is for valuables and constants. For example \sin sin , \cos cos , \tan tan , \ln ln , \gcd g cd , \int ∫ , \sum ∑ .
Problem Loading...
Note Loading...
Set Loading...
As known: f ′ ′ ( x ) + f ( x ) = 0 ⇒ f ( x ) = α sin ( x ) + β cos ( x ) = a cos ( x + b ) ⇒ g ( x ) = − a sin ( x + b ) So, replacing: F ( x ) = a ( cos 2 ( 2 x + b ) + sin 2 ( 2 x + b ) ) = a Given the condition: F ( 5 ) = 5 ⇒ F ( x ) = 5 ⇒ F ( 1 0 ) = 5